2017
DOI: 10.1364/ol.42.004446
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ablation of silica by plasmonic surface wave at low fluence

Abstract: Formation of ripples by ablation of surfaces of laser-irradiated materials is an example of ultrafast energy delivery. Herein, we report on fs-laser optical imprinting of periodic nano-grooves on silica substrate at only 25% of the laser ablation threshold via an interface plasmonic light localization at the ZnS film (top) interface with silica (bottom) by plasmonic surface wave. The nano-grooves were formed throughout ZnS with the same period and orientation imprinted onto the underlying silica. Based on a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Subsequent pulses interacting with these defects result scattered waves that interfere with each other, hence forming an intensity pattern that leads to the HSFL ripples. Also, the formation of periodic structures on glass surface under the ITO or ZnS layer was reported before [14,15]. In these cases, it was found that the underlying glass surface could be nano-fabricated using fluences amounting to ~25% of the ablation threshold of the glass.…”
Section: Introductionmentioning
confidence: 63%
“…Subsequent pulses interacting with these defects result scattered waves that interfere with each other, hence forming an intensity pattern that leads to the HSFL ripples. Also, the formation of periodic structures on glass surface under the ITO or ZnS layer was reported before [14,15]. In these cases, it was found that the underlying glass surface could be nano-fabricated using fluences amounting to ~25% of the ablation threshold of the glass.…”
Section: Introductionmentioning
confidence: 63%
“…Similar fluences have been used in the experimental demonstrations of various effects of metasurfaces 30 , 37 . Studies have also shown that by using appropriately structured elements or more resilient plasmonic materials, the damage threshold can even exceed 100 mJ/cm² 38 , 39 , allowing us to scale up the X-ray output by increasing the electromagnetic field strength even further. An unstructured graphene sheet supports a strong field of 3 GV/m; 31 , 32 however, the edges of nanoribbons present strong field enhancements (~30).…”
Section: Resultsmentioning
confidence: 99%
“…Within the electromagnetic scenario, the surface waves participating in establishing a standing pattern in interaction with the incoming light are often identified with the surface plasmon polaritons [89], coupling light and material. Recent advances proposed tuning of the optical properties of interfaces to allow for plasmonic processing [90]. Taking into account that particular optical conditions should apply to support plasmonic propagation in view of its dispersive behavior and the necessity to conserve momentum and energy, plasmonic waves were often considered to be the dominant contribution in the scattered surface wave.…”
Section: Focal Engineering and Near-field Processing: Sub-wavelength mentioning
confidence: 99%